TIC in teaching technology in basic and secondary education - Fabio Iván Moreno Orduz (Corporación Universitaria Minuto de Dios, 2004)
This article collects the synthesis from the investigation project called "application of the information and communication technologies to the technology teaching in the basic and secondary school" from the education faculty. It is going to be developed with the IX th semester students from the program informatics master degree. This projects wants to do an art state focuses in the application and use of the technologies in the technology and informatics area. It also wants to characterize the area in fifty Institutions from the capital district. With the results from this work we will design, build and validate the three learning ambiance for the area.